Attitudes toward anti-doping education among coaches of youth athletes - Onuma, N.; Nakajima, R.; Abe, M.; Matsubara, S.; Matsuo, E.; Shindo, D. (Journal of Sports Medicine & Doping Studies, 2019)
Objective: This study aimed to conduct a survey of coaches of youth athletes (e.g. middle school, high school, and university students) on the current state of and their attitudes towards anti-doping education, and on their level of familiarity with sports pharmacists (pharmacists with specialized knowledge on doping). A secondary aim was to examine the future directions of anti-doping education, including the roles of sports coaches and points at which they may intervene to resolve these issues. Methods: Sports coaches who taught health and physical education or coached extracurricular activities were asked to complete a questionnaire. In addition to general information such as the respondent`s age, their affiliated educational organization, number of years` experience of teaching and/or coaching, the types of sports they were involved in, and their level of athletic competition, data were collected on participants` experience with anti-doping education, their degree of familiarity with sport pharmacists, and their attitudes concerning the necessity of antidoping education and sports pharmacists. Results: Responses were obtained from 211 coaches. In response to a question that asked about their level of familiarity with sports pharmacists, 62.1% of the respondents said that they did not know of this profession. In response to a question on whether or not they had experience conducting classes on anti-doping, only 32.6% of coaches (n=31) said that they had such experience. On the other hand, responses to a question that asked about the necessity of anti-doping lectures showed that over 90% of coaches felt that they were needed. Furthermore, in response to questions on whether or not they would like to make use of antidoping teaching materials, should they be available, approximately 90% of coaches said that they would. Conclusion: Although coaches of youth athletes recognize the importance of anti-doping education, only a few coaches actually deliver such education. The results also revealed that coaches` level of familiarity with sports pharmacists was low. In the future, activities aiming to disseminate knowledge on anti-doping practices, not only to athletes but also to their coaches, will be necessary; these could include measures such as holding seminars and developing anti-doping teaching materials.